Katalog der in den Sammlungen des ehemaligen Deutschen Entomologischen Institutes aufbewahrten Typen - VI (Homoptera (exklusive Aphidina)). - Gaedike, Hannelore (Contributions to Entomology = Beiträge zur Entomologie, 1971)
There is presented a catalogue of type specimens of Homoptera (exklusive Aphidina) preserved in the collections of the former Deutsches Entomologisches Institut. Nomenclatural Acts esox Breddin, 321 (Capnodistes), Lectotype trucidula Breddin, 1903 (Conogonia), Lectotype aglaie Breddin, 1902 (Cosmoscarta), Lectotype arethusa Breddin, 1900 (Cosmoscarta), Lectotype briseis Breddin, 1903 (Cosmoscarta), Lectotype callirrhoe Breddin, 1901 (Cosmoscarta), Lectotype cassandra Breddin, 1903 (Cosmoscarta), Lectotype chryseis Breddin, 1903 (Cosmoscarta), Lectotype clematie Breddin, 1901 (Cosmoscarta), Lectotype crocale Breddin, 1902 (Cosmoscarta), Lectotype cyane Breddin, 1900 (Cosmoscarta), Lectotype erato Breddin, 1903 (Cosmoscarta), Lectotype hecate Breddin, 1903 (Cosmoscarta), Lectotype hippodamia Breddin, 1903 (Cosmoscarta), Lectotype hyale Breddin, 1901 (Cosmoscarta), Lectotype hyphinoe Breddin, 1902 (Cosmoscarta), Lectotype phiale Breddin, 1902 (Cosmoscarta), Lectotype pirene Breddin, 1900 (Cosmoscarta), Lectotype progne Breddin, 1903 (Cosmoscarta), Lectotype psecas Breddin, 1901 (Cosmoscarta), Lectotype sanguiniflua Breddin, 1899 (Cosmoscarta), Lectotype chlorizans Breddin, 1902 (Ennya), Lectotype fairmairei Breddin, 1902 (Ennya), Lectotype eos Breddin, 1902 (Eoscarta), Lectotype liternoides Breddin, 1902 (Eoscarta), Lectotype vulpeculus Breddin, 1901 (Gargara), Lectotype eos Breddin, 1901 (Huechys), Lectotype forcipata Breddin, 1901 (Mioscarta), Lectotype vitreolimbata Breddin, 1905 (Platypleura), Lectotype sarasinorum Breddin, 1901 (Pyrgauchenia), Lectotype foersteri Breddin, 1902 (Pyrgophyllium), Lectotype wallacei Breddin, 1902 (Pyrgophyllium), Lectotype locomotiva Breddin, 1901 (Sphongophorus), Lectotype machinula Breddin, 1901 (Sphongophorus), Lectotype aurorula Breddin, 1901 (Tettigonia), Lectotype centrivittata Breddin, 1899 (Tettigonia), Lectotype incula Breddin, 1901 (Tettigonia), Lectotype matutinula Breddin, 1903 (Tettigonia), Lectotype morosula Breddin, 1903 (Tettigonia), Lectotype nitidula Breddin, 1902 (Tettigoscarta), Lectotype